Fractionation and Characterization of Natural Antibacterial Compounds from Euphorbia hirta Linn (Asthma Plant) - Ojediran, G. O; Ojediran, O; Titilawo, O.Y; Shehu, Z; Titilawo M.A.; Titilawo M.A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Euphorbia hirta Linn (asthma plant) has for long been utilized as an herbal medicine globally in remedying and curing many an infection and disease in humans. Different parts of Euphorbia hirta for instance roots, leaves, saps, stems, flowers have been employed in ethnomedicine as it possesses a broad range of biological and pharmacological activities. The objective of this research study was to fractionate and characterize the natural antibacterial compounds from Euphorbia hirta plant. In the course of work, three different extracts (methanol, n-hexane and aqueous) of the plant were subjected to qualitative phytochemical analysis and the result signified the presence of metabolites. Crude extracts of the plant were tested against Escherichia coli, Klebsilla pneumoniae, Staphylococcus aureus by the cup plate agar diffusion assay method to explore the anti-microbial activity for its therapeutic applications. The plant exhibited an extensive antibiotic activity against the tested bacteria, calculated by measuring diameters of the zone with no microbial growth. The structure of compounds obtained from sample fractions through Column Chromatography were established using a combination of FT-IR and GC-MS. The following functional groups were detected; C-H vibration stretching at 2950cm-1 and 2974cm-1, CH2 bend at 1424cm-1, 1452cm-1 and 1454cm-1, C-H (stretch aliphatic) at 2917cm-1 and 2889cm-1, C-O (esters) at 1296cm-1, 1274cm-1 and 1275cm-1, C=O (carboxylic) at 1703cm-1, 1654cm-1 and 1714cm-1.The peaks obtained from GC-MS compared with corresponding library hits showed that the major compounds were vinyl laurate, monoethylhexyl phthalate and lauric acid triglyceride. From the results of this study, Euphorbia hirta plant can be a potential source of useful antibiotic drug.